2014
DOI: 10.4317/jced.17643850
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of alexidine, chlorhexidine and cetrimide against Streptococcus mutans biofilm

Abstract: Background: The use of antimicrobial solutions has been recommended to disinfect demineralized dentin prior to placing the filling material. The aim of this study was to evaluate the ability of several antimicrobials in controlling Streptococcus mutans (SM) biofilm formed in dentin. Methods: Antimicrobial activity of 0.2% and 2% chlorhexidine (CHX), 0.2% cetrimide (CTR) and 0.2%, 0.5%, 1% and 2% alexidine (ALX) was assayed on 1-week SM biofilm formed on standardized coronal dentin blocks. Results of SM biofilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Another bisbiguanide is alexidine (ALX), which has been previously used as a conventional mouthwash and contact lens solution [26]. Alexidine is similar to chlorhexidine but proven to have a faster bactericidal action and bacterial permeabilization because of the presence of two hydrophobic ethylhexyl groups in its structure [27].…”
Section: Alexidine -Alxmentioning
confidence: 99%
See 1 more Smart Citation
“…Another bisbiguanide is alexidine (ALX), which has been previously used as a conventional mouthwash and contact lens solution [26]. Alexidine is similar to chlorhexidine but proven to have a faster bactericidal action and bacterial permeabilization because of the presence of two hydrophobic ethylhexyl groups in its structure [27].…”
Section: Alexidine -Alxmentioning
confidence: 99%
“…Both agents observed eradicated the same amount of bacteria from dentin [29]. Furthermore, in a comparison of both agents, ALX shows lower toxicity when applied topically to corner tissue in vivo [26]. Recent studies have also reported that the interaction of ALX and NaOCl did not form an insoluble precipitate or PSA, as with CHX, and the color of the reacted solution changed transparent with decreasing ALX concentration.…”
Section: Alexidine -Alxmentioning
confidence: 99%